Rediffusion: Its Role And Function In Malaysian Broadcasting. - Cheong, Kim Chee (Universiti Sains Malaysia, 1982)
Rediffusion is an unique mass medium in Malaysia. It is the only private wired broadcasting station allowed to operate in Malaysia. Its areas of operation cover the market centres of Kuala Lumpur/Petaling Jaya, Ipoh and Penang/Province Wellesly.